Entrepreneurial Orientation and MSME’s Tourism Performance: The Mediating Role of Social Media Capability - Parlyna, Ryna; Susanto, Perengki; Abror, Abror; Marsal, Arif (Bright Publisher, 2024)
This study explores the mediating role of social media capability on entrepreneurial orientation (EO) and MSME’s tourism performance in DKI Jakarta Province, Indonesia (MP). MSMEs contributes largely to Indonesia's economy. However, these enterprises often struggle with limited resources leading to weaker performance. The research problem centers on identifying factors that can enhance the MP, mainly through EO and SMC. The objective is to investigate both EO's direct impact on MP and SMC's mediating role. Quantitative research was used, utilizing a survey-based method with data collected from 300 MSME owners and managers in the tourism sector. Structural Equation Modeling (SEM) was used to examine the relationships between EO, SMC and MP. The results reveal a favorable positive relationship between EO and MP, with a path coefficient (β) of 0.425 and a p-value of 0.000. It underscores the importance of EO in intensifying the MP. It also found that EO significantly affects SMC, with a path coefficient (β) of 0.353 and a p-value of 0.000. This suggests that MSMEs with a strong EO are expected to enhance SMC. SMC was also found to have a positive and favorable effect on MP, with a path coefficient (β) of 0.179 and a p-value of 0.001. This suggest that SMC is crucial for improving MP. It also confirmed the mediating role of SMC in the relationship between EO and MP, with an indirect path coefficient (β) of 0.063 and a p-value of 0.006. It proposed that EO directly enhanced MP through SMC. However, the study is narrowed by its focal point on a specific geographic area and sector, which may impact the relevancy of the results. Forthcoming study could address these limitations by exploring different contexts. This study contributes to broaden the literature on the mediating role of SMC in the EO- MP in DKI Jakarta, Indonesia.